4-6(2-3y)=2y-(4-5y)

Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.

2y-(4-5y)=4-6(2-3y)

Simplify each term.

Apply the distributive property.

2y-1⋅4-(-5y)=4-6(2-3y)

Multiply -1 by 4.

2y-4-(-5y)=4-6(2-3y)

Multiply -5 by -1.

2y-4+5y=4-6(2-3y)

2y-4+5y=4-6(2-3y)

Add 2y and 5y.

7y-4=4-6(2-3y)

7y-4=4-6(2-3y)

Simplify each term.

Apply the distributive property.

7y-4=4-6⋅2-6(-3y)

Multiply -6 by 2.

7y-4=4-12-6(-3y)

Multiply -3 by -6.

7y-4=4-12+18y

7y-4=4-12+18y

Subtract 12 from 4.

7y-4=-8+18y

7y-4=-8+18y

Subtract 18y from both sides of the equation.

7y-4-18y=-8

Subtract 18y from 7y.

-11y-4=-8

-11y-4=-8

Add 4 to both sides of the equation.

-11y=-8+4

Add -8 and 4.

-11y=-4

-11y=-4

Divide each term in -11y=-4 by -11.

-11y-11=-4-11

Cancel the common factor of -11.

Cancel the common factor.

-11y-11=-4-11

Divide y by 1.

y=-4-11

y=-4-11

Dividing two negative values results in a positive value.

y=411

y=411

The result can be shown in multiple forms.

Exact Form:

y=411

Decimal Form:

y=0.36‾

Solve for y 4-6(2-3y)=2y-(4-5y)